Pengembangan Buku Cerita Bergambar Digital Berbasis Pendidikan Karakter Religius Pada Mata Pelajaran SKI Di Kelas IV MI An-Nur Kota Cirebon - Linda Imamatul Ummah; Misbah Binasdevi; Heru Mudiyanto (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
This study aims to develop a digital picture storybook based on religious character education in the subject of Islamic Cultural History (SKI) in class IV MI An-Nur Cirebon City. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of media expert validation obtained a feasibility score of 94% (very feasible category), material expert validation of 96% (very feasible category), linguist validation results of 97% (very feasible category), as well as the results of student response trials of 91% (very good category) and an N-Gain value of 0.85 which stated very effective. The results showed that the digital picture storybook developed was considered feasible and effective to use as learning media. This media is expected to improve understanding of SKI material while instilling religious character values in students, as well as providing innovative alternatives in interesting and interactive learning